Gender and the Automobile – An Analysis of Non-work Service Trips - Colin Vance; Rich Iovanna (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Focusing on individual motorists in car-owning households in Germany, this analysis econometrically investigates the determinants of automobile travel for non-work service activities against the backdrop of two questions: 1) Does gender play a role in determining the probability of car use and the distance driven? 2) If so, how is this role mitigated or exacerbated by other socioeconomic attributes of the individual and the household in which they reside? Drawing on a panel of data collected between 1996 and 2003, we specify Heckman's sample selection model to control for biases that could otherwise arise from the existence of unobservable variables that determine both the discrete and continuous choices pertaining to car use.The results indicate that although women,on average, undertake more non-work travel than men, they undertake less of such travel by car, implying a greater reliance on other modes. Moreover, employment status, age, the number of children, automobile availability, and the proximity to public transit are all found to have significantly different effects on the probability of non-work car travel between men and women, but - with the exception of automobile availability - not on the distance driven.Taken together, these results suggest that policies targeted at reducing automobile dependency and associated negative externalities such as congestion are unlikely to have uniform effects across the sexes, findings having implications for both policy evaluation as well as travel demand forecasting.
Keywords: R21; R41; 330; Automobile travel; gender; Heckman model; Monte Carlo simulation; Verkehrsverhalten; Motorisierter Individualverkehr; Geschlecht; Schätzung; Deutschland